The Cdk inhibitor dinaciclib as a promising anti-tumorigenic agent in biliary tract cancer - Celina Ablinger; Daniel Neureiter; Theresa Mähr; Christian Mayr; Tobias Kiesslich; Nicole Maeding; Irina Valenta; Maximilian Ardelt; Fabian Wilhelm; Elen Neureiter; Markus Ritter; Johanna Pachmayr; et al. (Cancer Biology & Therapy, 2024)
Biliary tract cancer (BTC) is a rare malignancy with rising incidence. The therapeutic options are limited and the overall survival remains poor. Cyclin-dependent kinases, drivers of cell cycle and transcription have numerous biological functions and are known to be dysregulated in numerous tumor entities. Dinaciclib is a selective Cdk1/2/5/9 inhibitor with anti-tumor activity. In the present study, the efficacy of dinaciclib was tested on a comprehensive BTC cell-line model. The results indicate a heterogeneous expression pattern of Cdk1/2/5/9, as well as various differentiation tumor markers in BTC cells. We demonstrated that dinaciclib reduces cell viability, ATP levels, and proliferation rates. Moreover, dinaciclib induces apoptosis via increased caspase 3/7 activity and reduced expression levels of the anti-apoptotic protein Mcl-1 in a concentration- and cell line -dependent manner. 3D cell culture confirms the cytotoxic impact of dinaciclib under more physiologic tumor conditions. Additionally, dinaciclib affects different cell growth regulators like EGFR and STAT3 on gene and protein level, thus decreasing tumor growth. In summary, our study indicates that dinaciclib acts as a promising anti-tumorigenic agent in 2D and 3D in vitro BTC models and thus encourages further investigation.